2008
DOI: 10.1161/hypertensionaha.107.097865
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-Converting Enzyme C-Terminal Catalytic Domain Is the Main Site of Angiotensin I Cleavage In Vivo

Abstract: Abstract-Angiotensin-converting enzyme (ACE) plays a central role in the production of the vasoconstrictor angiotensin II. ACE is a single polypeptide, but it contains 2 homologous and independent catalytic domains, each of which binds zinc. To understand the in vivo role of these 2 domains, we used gene targeting to create mice with point mutations in the ACE C-domain zinc-binding motif. Such mice, termed ACE13/13, produce a full-length ACE protein with tissue expression identical to wild-type mice. Analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
78
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(89 citation statements)
references
References 31 publications
4
78
1
3
Order By: Relevance
“…1, C and F), suggesting that each catalytic domain of ACE regulates the activity of the other, and both domains are required for normal substrate recognition and degradation. Mice with a selective inactivation of either the N-or C-domain of ACE were generated, and the C-domain was demonstrated to be the main site of angiotensin I cleavage (18,22), which is consistent with our in vitro finding. However, the role of the N-domain of ACE toward A␤42 to A␤40 conversion in vivo needs to be addressed.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…1, C and F), suggesting that each catalytic domain of ACE regulates the activity of the other, and both domains are required for normal substrate recognition and degradation. Mice with a selective inactivation of either the N-or C-domain of ACE were generated, and the C-domain was demonstrated to be the main site of angiotensin I cleavage (18,22), which is consistent with our in vitro finding. However, the role of the N-domain of ACE toward A␤42 to A␤40 conversion in vivo needs to be addressed.…”
Section: Discussionsupporting
confidence: 87%
“…1C). F-ACE was found to have the highest Hip-His-Leu-degrading activity and C-ACE had 63% ACE activity compared with F-ACE, whereas N-ACE had a significantly reduced ACE activity, confirming the finding of the ACE C-domain as the main site of angiotensin I cleavage in vivo (18) (Fig. 1C).…”
Section: Ace N-domain But Not C-domain Converts A␤42 To A␤40-supporting
confidence: 73%
See 1 more Smart Citation
“…The MEROPS database classification is clan MA, subclan MA(E), family M2, and peptidase XM02-001 (Rawlings et al, 2008). Expression of each ACE domain in Chinese hamster ovary cells and the creation of mice with ACE genetic mutations has shown that each domain binds zinc and is independently catalytic (Wei et al, 1991a;Fuchs et al, 2004Fuchs et al, , 2008.…”
Section: E Structure Of Angiotensin-converting Enzymementioning
confidence: 99%
“…[9][10][11] ACE contains two homologous domains (C-and N-domain), each bearing a catalytic site, that have been demonstrated to have differential enzymatic activities. In brief, work with both N-domain and C-domain knockout mice 12,13 has indicated that Ang 1-10 hydrolysis to Ang 1-8 is predominately catalysed by the C-domain whilst the antifibrotic tetrapeptide N-acetyl-seryl-aspartyl-lysylproline (Ac-SDKP) is a highly specific substrate for the N-domain catalytic site. 14 As presently prescribed ACEi target both domains similarly, design of C-domain selective inhibitors is a logical step toward improving the side effect profile of ACE inhibition.…”
mentioning
confidence: 99%